AI’s impact on science education: a study of ant and bee mindsets in UAE science classrooms - Alarabi, Khaleel; Alabidi, Suzan; Tairab, Hassan; Pagani, Linda S.; AlSadrani, Badriya; Abu Khurma, Othman (Frontiers in Education, 2025)
IntroductionAlthough Artificial intelligence (AI) has the potential to revolutionize educational practices worldwide, particularly within the science domain, the integration of such technologies in education remains a challenge. This study investigates science teachers’ perspectives regarding AI and examines how its integration influences teaching and learning processes. The research employs the metaphor of a dedicated ant farm and a co-operative beehive to analyze the potential of AI for enhancing science education. Two primary mindsets are identified: ant-like and bee-like thinking. This conceptualization illustrates how science teachers in the UAE perceive the integration of AI into education. Two research questions guided the study design: (1) How do science teachers perceive the impact of AI on science education’s effectiveness and outcomes? (2) What insights do science teachers have regarding the integration of AI into traits related to ant-like or bee-like thinking?MethodsConsequently, a cross-sectional survey was carried out, designed to collect data from 104 science teachers who voluntarily participated in this study using a specifically developed and validated questionnaire.ResultsThe findings indicate that the majority of teachers reported a high or extraordinarily high level of understanding of the impact of AI integration in science education, which implies strong agreement with its potential influence.DiscussionThe study’s findings offer a metaphor-based framework that showed a wide range of responses to the ant-like thinking and bee-like thinking metaphors, highlighting the complexity of science teacher perceptions. These findings diagonalized the need for more evident conceptual framing and further research on how such metaphors (heuristic tools) can be used to influence teacher understanding and classroom application of AI in a science learning context.